Nursing technique and growth environment of Rabbit fish (Siganus guttatus) in the area of Tam Giang lagoon, Thua Thien Hue - Stattin, Cecilia (SLU/Dept. of Animal Nutrition and Management (until 231231), 2012)
Summary In the area to the east of Hue city, in Vietnam, lays Tam Giang lagoon, one of Asia's largest lagoons, with an area of 22,000 hectares. This lagoon is suitable for aquaculture. One reason for this is because the salinity differs from sweet to salty in different parts of the lagoon. The Vietnamese Government advocates an increase in environmentally-friendly aquaculture and the fish Siganus guttatus (Rabbit fish) is a candidate for this. This fish eats mainly algae and can be cultivated in a polyculture. The purpose of this master thesis was to investigate how the fish S. guttatus are cultivated in nurseries. Focus was set on a farm located near the town of Tuan An, which cultivated the fish in cement tanks. What would be examined was growth in length and weight and various parameters of water quality where the fish were held. These results would then be compared to farms where fish were reared in earthen ponds on the shores of the Tam Giang lagoon. Only water quality and interviews with the farmers were made on the farms rearing S. guttatus in earthen ponds. Also an economic evaluation would be performed for the different farms. One nursery (farm 1) rearing S. guttatus in cements tanks was visited during an 8 week period. During these 8 weeks the fish grew 3.1 cm and 1.7 g. The mean water parameters were: temperature: 28.4 ° C, salinity: 20.6 ‰, alkalinity: 140 ppm, pH: 7.7, DO 4.5 mg / L, TAN: 0.4 ppm. Three other farms (farm 2, 3 and 4) were visited for interviewing the farmer cultivating Rabbit fish in earthen ponds. At 2 of those farms (farm 2 and 3) also the water quality was analysed according to the same parameters as farm 1. The results from farm 2; temperature: 30 °C, salinity: 13 ‰, alkalinity: 60 ppm, pH: 8, DO: 3 mg/L, TAN: 0.2 ppm. The results from farm 3; temperature: 32 °C, salinity: 16 ‰, alkalinity: 120 ppm, pH: 7.5, DO: 4 mg/L, TAN: 0.2 ppm. The management on the farms differed on some points. Farm 1 produced its own concentrate feed during the first month, consisting of fish meal, rice bran, cassava root meal, vitamins and probiotic (Bacillus subtilis). After the first month the fish got fed the same as on the other farms; industrially produced pelleted concentrate feed. In Addition, the fish were fed seaweed from the family of Gracilaria. None of the farms added chemicals to the ponds during cultivation of the Rabbit fish. One farm added saponins to the water between different cultivation batches. This to eradicate the fish that had swam in to the pond when the pond was refilled with new water. Two of the farms changed the pond water regularly, while a third added water from the lagoon to the pond after heavy rain. The fourth farm changed nothing in the pond during the rearing period. Profits did not differ significantly between the farms that were reared in earthen ponds. However, the farm with cement tanks produced much higher profits per square meter. It was difficult to draw conclusions about differences between the different farming methods because of too few data.